Studium vlivu složení lehkých vláknobetonů na fyzikálně-mechanické vlastnosti - Šindelek, David (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Bakalářská práce se zabývá studiem lehkých konstrukčních betonů doplněných o ocelová vlákna, kde sleduje jejich dopad na fyzikální a mechanické vlastnosti. Práce je rozdělena do dvou částí, teoretickou a praktickou. Teoretická část je zaměřena na vlastnosti a navrhování lehkých betonů v pevnostní třídě nad 35MPa s objemovou hmotností ve třídě D 1,8. Dále se zaměřuje na zvýšení houževnatosti cementových kompozitů, formou aplikace ocelových vláken v různých dávkách a délkách. V praktické části byly navrženy receptury ve dvou pevnostních třídách 35/38 D 1,8 a 45/50 D 1,8 s použitím ocelových vláken KrampeHarex v dávkách 25 a 30 kg/m3, kde byl sledován jejich dopad na vývoj pracovního diagramu a pevnost v tlaku po 28 dnech.

This bachelor thesis deals with a study of light construction concrete with an addition of steel fibre which monitors its impact of the physical mechanical properties. The work is divided into two parts, theoretical and practical. The theoretical part is focused on characteristics and a design of light concrete within the class 35MPa and over with the density within the class of D1,8. Furthermore, it focuses on the increase of toughness of cementitious composites with the form of application of steel fibre in different doses and lengths. In the practical part, formulas of two strength classes 35/38 D 1,8 and 45/50 D1,8 were designed with the help of the steel fibre Krampeharex in doses of 25 and30 kg/m3, and where there were both its impact of the working diagram as well as the compressive strength monitored for the duration of twenty-eight days
The study of the influence of the composition of the lightweight fiber concrete physical and mechanical properties
Keywords: Beton; lehký beton; lehké kamenivo; ocelová vlákna; pevnost v tlaku; pevnost v tahu; Concrete; lightweight concrete; lightweight aggregate; steel fibers; compressive strength; post-cracking flexural tensile strength